Effectiveness of Spiritual Emotional Freedom Technique (SEFT) In Reducing Students' Anger - Siti Nuroh; Zulkipli Lessy; Muhamad Fajar Bastian (Faculty of Ushuluddin and Humanities, 2022)
Because of unstable emotions, teenagers have sometimes fallen in a precarious situation, such as violating societal rules and religious norms. Managing emotion therefore is a pivotal aspect to nurture them towards maturity. This study aims to (1) determine the ability of controlling students’ anger; (2) measure effectiveness of the use of Spiritual Emotional Freedom Technique (SEFT) in reducing students’ anger, and (3) describe the applicability of Spiritual Emotional Freedom Technique (SEFT) in student learning. By using the qualitative approach, data collection methods are in-depth interviews, observations, and documentation. The results of this study show that the ability of students in controlling their anger is relatively low, and the applicability of the SEFT in student learning can be done through developing a Learning Implementation Plan (RPP) in supporting their spiritual aspects even though it is only a nurturing effect and not an instructional one because using only the SEFT in reducing students’ angry emotions is considered ineffective.